Accessible Hyperlinks and Search Engine Rankings: An Empirical Investigation - Cebeci, Goker; Diri, Banu (IEEE, 2025)
This study investigates the impact of accessibility features of internal links on a website's Search Engine Results Page (SERP) ranking. To test the hypothesis that accessibility influences SERP ranking, a labeled dataset was created to measure internal link accessibility. In creating this dataset, internal links on websites were matched with their corresponding subpages listed by search engines to complete the labeling process. Accessibility metrics such as is_unique, contrast_ratio, and text_clarity were extracted for the internal links using machine learning techniques. Analysis of the data suggests that accessibility features may indeed influence SERP rankings. The labeled dataset created in this study will serve as a resource for future research on internal link accessibility and SERP ranking.
Keywords: Accessibility; SEO; SERP; Computer Science; Engineering; Telecommunications